Clinical implications of genomics for cancer risk genetics. Issue 6 (June 2015) - Thomas, David M; James, Paul A; Ballinger, Mandy L
Summary: The study of human genetics has provided substantial insight into cancer biology. With an increase in sequencing capacity and a reduction in sequencing costs, genomics will probably transform clinical cancer genetics. A heritable basis for many cancers is accepted, but so far less than half the genetic drivers have been identified. Genomics will increasingly be applied to populations irrespective of family history, which will change the framework of phenotype-directed genetic testing. Panel testing and whole genome sequencing will identify novel, polygenic, and de-novo determinants of cancer risk, often with lower penetrance, which will challenge present binary clinical classification systems and management algorithms. In the future, genotype-stratified public screening and prevention programmes could form part of tailored population risk management. The integration of research with clinical practice will result in so-called discovery cohorts that will help identify clinically significant genetic variation.